2008
DOI: 10.1097/ppo.0b013e3181867628
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Epidemiology of Renal Cell Cancer

Abstract: We analyzed renal cell cancer incidence patterns in the United States and reviewed recent epidemiologic evidence with regard to environmental and host genetic determinants of renal cell cancer risk. Renal cell cancer incidence rates continued to rise among all racial/ethnic groups in the United States, across all age groups, and for all tumor sizes, with the most rapid increases for localized stage disease and small tumors. Recent cohort studies confirmed the association of smoking, excess body weight, and hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
197
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(211 citation statements)
references
References 200 publications
(233 reference statements)
5
197
0
9
Order By: Relevance
“…Several genetic syndromes predisposing to familial RCC have been identified. The most common of the hereditary syndromes are germline mutations in the von Hippel -Lindau (VHL) tumoursuppressor gene on chromosome 3p, which is associated exclusively with the clear cell histological subtype (Czene and Hemminki, 2002;Hung et al, 2007;Chow and Devesa, 2008). In addition to RCC, individuals with this germline mutation are at an increased risk for developing tumours of the central nervous system, retina, endolymphatic sac of the inner ear, broad ligament, Family history of cancer and RCC risk by race S Karami et al adrenal glands, and pancreas (Kaelin, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several genetic syndromes predisposing to familial RCC have been identified. The most common of the hereditary syndromes are germline mutations in the von Hippel -Lindau (VHL) tumoursuppressor gene on chromosome 3p, which is associated exclusively with the clear cell histological subtype (Czene and Hemminki, 2002;Hung et al, 2007;Chow and Devesa, 2008). In addition to RCC, individuals with this germline mutation are at an increased risk for developing tumours of the central nervous system, retina, endolymphatic sac of the inner ear, broad ligament, Family history of cancer and RCC risk by race S Karami et al adrenal glands, and pancreas (Kaelin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Since 1950, in the United States, there has been a 126% increase in RCC incidence (Paglino et al, 2007), with higher rates reported among African Americans (AAs) than among Caucasians (Chow and Devesa, 2008). The increasing rates of RCC over time may reflect, in part, the increasing use of imaging modalities (Paglino et al, 2007;Chow and Devesa, 2008;Patard, 2009). However, as the increase involves all tumour sizes, not just those at the local stage (Patard, 2009), imaging modalities alone do not entirely explain the increase.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…At first presentation, 45% of patients will have localised disease, 25-30% will have locally advanced disease with lymph node or local organ involvement and around 25% patients have metastatic disease [2,3]. In the past, nephrectomy was offered mainly as a means of palliation to relieve the pain from local infiltration or haematuria when the conservative measures failed.…”
Section: Introductionmentioning
confidence: 99%